BODIES AND DATA: THE DIGITAL SOVEREIGNTY OF THE INDIAN STATE - Prasad, Revati (AoIR Selected Papers of Internet Research, 2021)
In February 2019, the Government of India released a draft e-commerce policy that boldly proclaimed, “India and its citizens have a sovereign right to their data,” (Department for Promotion of Industry and Internal Trade, 2019) a right that could not extend to non-Indians. The draft policy was one of many in recent years that have mandated data localization, protectionism or other measures of greater national control over the digital economy in India. These actions are widely read as a nation-state asserting its sovereignty in the digital realm against the power of US-based global tech firms. They are sold in geopolitical terms, a digital sovereignty that challenges digital colonialism. I argue that the Indian state’s project of digital sovereignty must also be understood as biopolitical. I connect the Indian state’s regulation of the digital economy, exemplified by the 2019 draft of the e-commerce policy to its regulation and control of bodies, specifically through the biometric ID, Aadhaar, and its proliferating uses. I read these state actions collectively as a process through which the Indian state is engaged in altering what it is to be sovereign and its subject. When “digital” appends sovereignty, it is not merely a new terrain upon which to exert power, nor is it an unbridled force that the state must contend with, it is the means through which the Indian state enacts its project(s) of domination.